Students' Interest in Physical Education Learning at State Junior High School 1 Banjarbaru, South Kalimantan - Muhammad, Andi; Kahri, Ma’ruful; Rahmadi, Rahmadi (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This research aims to determine students' interest in Physical Education at SMP Negeri 1 Banjarbaru. This type of research is quantitative descriptive. The population in this research was 320 students at SMP Negeri 1 Banjarbaru class VIII. The sampling technique uses the Slovin formula with an allowance of 20% for a sample size of 25 students. The questionnaire's indicators of interest in learning are divided into four indicators: 1) Feelings of joy, 2) student interest, 3) Attention, and 4) student involvement. The number of statements designed was 27 statements. This research shows students' interest in learning Physical Education at SMP Negeri 1 Banjarbaru, with an average of 62% in the strong category.